Diabetes and dementia: current data - N.V. Pashkovska; V.M. Pashkovskyy (Mìžnarodnij Endokrinologìčnij Žurnal)
This review analyzes current data on the epidemiology, pathogenesis, clinical features, and approaches to the treatment of cognitive impairments in diabetes mellitus (DM). DM is recognized as an independent risk factor for dementia, particularly Alzheimer’s disease and vascular dementia, increasing their likelihood by 50–91 %. The mechanism of cognitive disorders in DM includes brain insulin resistance, hyperglycemia, beta-amyloid accumulation, tau pathology, oxidative stress, vascular dysfunction, and neuroinflammation. Insulin resistance disrupts signaling pathways (IRS-1/PI3K/AKT), contributing to neurodegeneration, while chronic hyperglycemia damages the endothelium, accelerates atherosclerosis, and increases the risk of dementia due to ischemic neuronal damage. According to clinical guidelines, cognitive impairment screening is recommended for all individuals with DM over 65 years old (earlier if mental changes are observed) using psychodiagnostic tests. Diagnosis also includes neuroimaging, cerebral hemodynamics analysis, and cerebrospinal fluid biomarker testing (beta-amyloid, tau protein), while PET scans for amyloid and tau, along with neuronal damage markers, are promising for early detection and staging of the disease. Treatment strategies should be individualized, focusing on glycemic control (target HbA1c < 8.0 % in the elderly), minimizing hypo-/hyperglycemia, and preventing vascular complications. Dementia treatment involves combining antidiabetic therapy with standard approaches: cholinesterase inhibitors, NMDA receptor antagonists, or anti-amyloid monoclonal antibodies. This strategy aims to slow cognitive decline and improve patient quality of life. Metformin, as a pathogenetically relevant antidiabetic drug, plays a key role not only in glycemic control but also in dementia treatment, as it reduces amyloid burden, suppresses inflammation, activates the AMPK pathway, stimulates neurogenesis, and improves cognitive function even in non-diabetic patients. Long-term metformin use is associated with a 29–84 % reduced risk of dementia, depending on therapy duration, and its combination with other drugs may provide synergy in slowing neurodegeneration. Dementia prevention includes lifestyle modifications (physical activity, healthy diet), correction of harmful habits, avoiding environmental risks, and controlling body weight, blood pressure, and lipid levels.